Pharmacological ascorbate combined with rucosopasem selectively radio-chemo-sensitizes NSCLC via generation of H2O2 - C.F. Pulliam; M.A. Fath; S. Sho; S.T. Johnson; B.A. Wagner; M. Singhania; A.L. Kalen; K. Bayanbold; S.R. Solst; B.G. Allen; B.N. George; J.M. Caster; et al. (Redox Biology)
Differences in cancer and normal cell oxidative metabolism provide a unique therapeutic opportunity for developing combined modality approaches with redox-active small molecules as radio-chemosensitizers that are well-tolerated by normal tissues. Pentaazamacrocyclic Mn (II)-containing (MnPAM) superoxide dismutase (SOD) mimetics and pharmacological ascorbate given IV to achieve [mM] plasma levels (pharmacological ascorbate: P-AscH‾) have been shown to act individually as cancer cell radio- and chemosensitizers via the generation of H2O2 in vivo. The current study shows that the combination of newly developed MnPAM dismutase mimetic, rucosopasem manganese (RUC) with P-AscH‾ radio-sensitizes non-small cell lung cancer cells (NSCLC) and increases steady state levels of intracellular H2O2 with no additional toxicity to normal human bronchial epithelial cells (HBECs). Conditional over expression of catalase (CAT) in H1299T CATc15 cells demonstrates that the combination of RUC and P-AscH‾ causes radio-sensitization through an H2O2-dependent mechanism. Interestingly, RUC combined with P-AscH‾ demonstrates more than additive cytotoxicity in both H1299T and A549 NSCLC cells, but conditional over-expression of ferritin heavy chain (FtH) protected only the H1299T, and not the A549, from this toxicity. Most importantly, the combination of RUC + P-AscH‾ was found to sensitize both H1299T and A549 cell types to radio-chemotherapy with cisplatin (CIS) + etoposide (ETOP). Finally, in H1299T NSCLC xenografts the combination of RUC + P-AscH‾ with CIS + ETOP and 12 × 2 Gy radiation significantly inhibits tumor growth and increased median overall over survival. These results support the hypothesis that selective MnPAM dismutase mimetic + P-AscH‾ enhances the efficacy of radio-chemotherapy in NSCLC through a mechanism governed by redox active metals and H2O2 production.